Nilai Nilai Karakter Dalam Lirik Lagu Husein Mutahar Pada Buku Siswa Sekolah Dasar - Dhea Anggita Vernanda; Fifi Alaydia Putri; Kurnia Puji Lestari; Rian Damariswara (Badan Penerbit STIEPARI Press, 2023)
In developing children's character, the role of the teacher also has an important role as the main figure in schools in guiding and educating children. Giving songs to instill character values according to the level of child development. Husein Mutahar's children's song was chosen as the object of research because of several considerations, namely as follows: (1) Husein Mutahar's children's song can be learned at all levels of education, (2) Husein Mutahar's children's song is able to evoke a spirit of nationalism, (3) children's song Husein Mutahar's work tells about gratitude because Indonesia has become independent, (4) awakens a sense of nationalism and love for the motherland, especially Indonesian youth. This type of research is literature research with a qualitative approach, because it is done by reading, researching, understanding, criticizing and evaluating. The analytical method used is qualitative analysis. Based on the results and discussion, it can be concluded that there are three children's songs by Husein Mutahar in the elementary school students' books. There are 13 character values based on character values.